A hemocyte-specific cathepsin L-like cysteine protease is involved in response to 20-hydroxyecdysone and microbial pathogens stimulation in silkworm, Bombyx mori. (March 2021) - Pan, Guangzhao; Zhang, Kui; Li, Chongyang; Hu, Xin; Kausar, Saima; Gu, Hongyu; Yang, Liqun; Cui, Hongjuan
Graphical abstract: Highlights: A novel cathepsin L- like was cloned and identified in silkworm. Cat L-like is highly and specifically expressed in hemocytes. Cat L- like could be induced by 20-E. Expression of Cat L- like as up-regulated during bacterial infection. Abstract: Cathepsin L protease belongs to the papain-like cysteine proteases family, plays indispensable roles in animals' pathological and physiological processes. However, little is known about Cathepsin L in silkworm, Bombyx mori . Herein, a novel Cathepsin L- like ( Cat L- like ) was cloned and identified from silkworm by the rapid amplification of cDNA ends (RACE). Cat L- like contains an intact open reading frame (ORF) of 1 668 bp and encodes 556 amino acid residues, consisting of a signal peptide, typical cathepsins' inhibitor_I29, and pept_C1 domain. Cat L- like is specifically and highly expressed in hemocytes. The cathepsin (including Cathepsin L, B, and H) crude extract from hemocytes had typical substrate specific catalytic activities and were sensitive to pH and temperature. Cat L- like up-regulated considerably after 20-hydroxyecdysone (20-E) administration, indicating that Cat L- like may be regulated by insect hormone. The responses of Cat L- like against bacterial infection suggest it may play essential roles in silkworm immunity. Overall, our studies provide a theoretical basis and insights to further investigate the functions of Cat L- like and in insects' innate immunity mechanisms.